Sharing knowledge and experiences guide to manage disasters - Lochana, C.A.S. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
Sri Lanka is prone to natural disasters commonly caused by floods, cyclones, landslides, droughts and coastal erosion with increasing losses to life and property. The devastation caused by the 2004 tsunami took Sri Lanka by surprise, warning that Sri Lanka is also vulnerable to low-frequency, high-impact events. Only two projects, Hazard Mapping Project by the National Building Research Organization (1991-1996) and Sri Lanka Urban Multi-Hazard Disaster Mitigation Project (1997-2003), can be considered somewhat successful in proactive disaster mitigation. In May 2005, the Sri Lanka Disaster Management Act provided a solid legislative and institutional arrangement for disaster risk management, establishing a powerful National Council for Disaster Management. In November 2005, the Ministry of Disaster Management was established to provide leadership. The Ministry of Disaster Management declared its Road Map in December 2005 focusing on seven thematic components. Proper implementation of this Road Map will go a long way towards a safer Sri Lanka.
Keywords: Disaster management, institutional support, Sri Lanka